The Effect of Education, HDI, Economic Growth, and Minimum Wage on Unemployment: A Study of 10 Provinces in the Sumatra Region: A Study of 10 Provinces in the Sumatra Region - Manihuruk, Frido Evindey; Gultom, Rona Hinirim; Ariza, Dafa; Lubis, Putri Kemala Dewi (Program Studi Akuntansi Universitas Islam Lamongan, 2024)
Unemployment is a very complex problem, especially in the Sumatra region with an average unemployment rate that exceeds the average in Indonesia. The purpose of this quantitative research is to analyze the effect of education, the human development index, economic growth, and minimum wage on unemployment in Sumatra region. This study uses secondary data obtained from the Indonesian Central Bureau of Statistics and analyzed using panel data regression by applying the Fixed Effect Model. The results showed that education and economic growth have a negative effect and HDI and minimum wage have a positive effect on unemployment. In this study, it was found that HDI and economic growth have a significant influence on unemployment, while education and minimum wage have an insignificant influence. Based on the R-squared value of 0.9137 which interprets that the independent variable affects the dependent variable by 91.37%, the remaining 8.63% is influenced by other variables outside this study. The results of this study are expected to be used as a basis for policy-making and as a literature review in further research related to unemployment.